Lidocaine Clearance as Pharmacokinetic Parameter of Metabolic Hepatic Activity in Patients with Impaired Liver - Jovanović, Marija; Kovačević, Milena; Vezmar Kovačević, Sandra; Palibrk, Ivan; Bjelanović, Jasna; Miljković, Branislava; Vučićević, Katarina (Journal of Medical Biochemistry, 2022)
Background The study aimed to estimate lidocaine (LID) pharmacokinetic parameter values in patients with impaired liver function, and to assess change in parameters related to the surgical intervention.Methods Patients with impaired liver function were subject to the test prior to, 3 and 7 days after the intervention. LID was administered in single i.v. dose of 1 mg/kg. Blood samples were collected at 15, 30 and 90 minutes after drug administration. Non-compartmental analysis was applied for calculating the pharmacokinetic parameters.Results The study included 17 patients with the diagnosis of cirrhosis and 41 patients with liver tumor. In both groups of patients, the values of the coefficients of correlation show the best correlation between CL and Child-Pugh score (-0.693, p
Keywords: liver failure; lidocaine; pharmacokinetics